Weed management strategies for castor bean crops - Augusto Guerreiro Fontoura Costa; Valdinei Sofiatti; Cleber Daniel de Góes Maciel; Juliana Parisotto Poletine; João Igor de Sousa (Acta Scientiarum. Agronomy, 2014)
Castor bean crops are agriculturally relevant due to the quality and versatility of their oil, both for the chemical industry and for biodiesel production. Proper weed management is important for both the cultivation and the yield of castor bean crops; therefore, the intention of the present work is to review pertinent information regarding weed management, including the studies regarding weed interference periods, chemical controls for use in different crop production systems and herbicide selectivity, for castor bean crops. Weed science research for castor bean crops is scarce. One of the main weed management challenges for castor bean crops is the absence of herbicides registered with the Ministry of Agriculture, Livestock and Food Supply (MALFS). Research for viable herbicides for weed control in castor bean crops should be directed by research and/or rural extension institutions, associations and farmers cooperatives, as well as by manufactures, for the registration of these selective herbicides, which would be primarily used to control eudicotyledons in castor bean crops. New studies involving the integration of weed control methods in castor bean also may increase the efficiency of weed management, for both small farmers using traditional crop methods in the Brazilian Northeast region, as well as for areas with the potential for large scale production, using conservation tillage systems, such as the no-tillage crop production system.